اقبال اور مولانا رومی: فارسی حکمت، تصوف اور اسلامی فلسفہ کا تقابلی مطالعہ: Iqbal and Maulana Rumi: A Comparative Study of Persian Wisdom, Sufism, and Islamic Philosophy (Contemporary Journal of Social Science Review, 2025)
This research undertakes a comparative study of two towering intellectual and spiritual figures of the Muslim world — Allama Muhammad Iqbal and Maulana Jalaluddin Rumi. Both thinkers, though centuries apart, share deep roots in Persian literature, Islamic philosophy, and Sufism. The study explores how Iqbal, the visionary poet-philosopher of the 20th century, found intellectual and spiritual inspiration in the teachings and mystical worldview of Rumi, whom he revered as his spiritual guide or Murshid. The research investigates the philosophical underpinnings of their poetry, particularly their shared emphasis on selfhood (khudi), divine love, and the evolution of the human soul. It also examines how both thinkers employed Persian as a vehicle for expressing profound metaphysical and ethical insights. Through a comparative analysis of their poetry and philosophical ideas, this study seeks to identify both the similarities and differences in their understanding of spiritual development, divine reality, and the role of humanity in the cosmic order. The methodology adopted includes textual analysis of primary Persian texts and critical interpretations by contemporary scholars. This exploration contributes to a richer understanding of the intellectual continuity within Islamic thought, showing how classical Sufi philosophy informed modern Muslim identity and resistance to colonialism, particularly in Iqbal's thought.Ultimately, this study highlights the enduring relevance of Rumi’s and Iqbal’s ideas for contemporary spiritual, ethical, and philosophical discourse in the Islamic world and beyond.